Turkish as a Technology Language - Osman Özdemir (Türkiyat mecmuası, 2024)
The aim of this study is to examine the status of Turkish as a language of technology from the perspective of the past to the present and within the framework of the basic concepts of being a language of technology. Accordingly, the topic is discussed within the framework of technology, language, thought, science, and the relationship between technology and language. In this study, in which a basic qualitative research method was used, document analysis was preferred as a data collection tool. By considering relevant studies in the literature, an inductive data analysis was used to draw a framework for the issue of Turkish as a language of science. In the first part of the study, the basic concepts of language and technology were discussed from a historical perspective. Then, the status of language as a technology, the effect of language on thought and technology with its vocabulary set, technology shaping language and thoughtas a discourse, human language technology, and the contribution of technology to language by creating new concepts were discussed. In the findings section, the current situation of Turkish was analyzed through the issue of a language being a language of technology. Accordingly, the mutual relationship between Turkish and technology was discussed. In this section, the contributions of Turkish to technology and the effects of technology on Turkish were analyzed in two ways. Then, the impacts of Turkish on science and technology from past to present were mentioned from a historical perspective. Finally, the possibilities of Turkey as a future language of technology in the future were emphasized. In this direction, the potential of Turkish to be a language of technology in terms of its structure and its relationship with its processing as a language of science were mentioned.